Pengaruh Corporate Governance, Profitabilitas, dan Capital Intencity terhadap Tax Avoidance - Nasichah, Fadlilatun Nasichah; umaimah, Umaimah (Journal of Culture Accounting and Auditing, 2023)
This study aims to examine the effect of independent commissioners, audit committees, profitability and capital intensity on tax avoidance. This research is a quantitative research, the type of data used is secondary data obtained from the company's annual report. The population in this study are manufacturing companies in the consumer goods industry sector which are listed on the Indonesia Stock Exchange (IDX) for 2020-2022. A total of 111 samples were determined using the purposive sampling method and analyzed using multiple linear regression using the SPSS analysis tool. The results of the study show that independent commissioners have significant effect on tax avoidance, while audit committees, profitability and capital intensity have no significant effect on tax avoidance.